Issues for the long-term management of Social Business Documents - Verena Hausmann; Susan Williams (International Journal of Information Systems and Project Management, 2016)

(untitled)
Social business documents are currently one of the fastest growing content types within organizations. As carriers of important business information they require systematic management to ensure their content is available, accurate and protected over the long-term. To achieve this requires a deep understanding of their structure, nature and use. In this paper we present the findings of a preliminary study of social business documents. The aim of the study is to understand how social business documents are structured and to identify the issues and challenges that surround their management. Through an analysis of social business documents in four different systems we identify and compare their structural components from a user perspective. From this cross document/cross system analysis we develop a conceptual model for social business documents and identify issues for their long-term management. Our findings also identify the need for more in-depth modeling for which we propose methods to assist in understanding the syntactic and semantic structure of social business documents and how these change over the life of a social business document.